PENGARUH PENGGUNAAN BACKING KERAMIK TERHADAP KEKUATAN UJI BENDING PADA ASTM A36 DENGAN MENGGUNAKAN PROSES SMAW - Defri Herdiansyah; Nur Yanu Nugroho (JURNAL JALASENA, 2022)
Welding with SMAW is usually used to fulfill the needs of home scale and large projects. When welding metal on large structures such as ships, the welder often has to weld back and forth on both sides of the ship, thus wasting time and energy. Therefore, a ceramic backing that serves as a support and molds good weld results. This saves budget and speeds up the welding process. From the above discussion, it is necessary to examine the effect of using ceramic backing on the strength of the ASTM A36 steel bending test results using SMAW welding. This research is an experimental research and the data analysis technique used is analysis of variance (ANOVA). From the results of the tensile test, there is an effect of strength on ASTM A36 steel when viewed from the average value of Ultimate tensile strength found in specimen testing that does not use backing, the average value obtained is 451.893 N/mm2. test analysis of variance, It is known that the calculated F is 5.501 and the F table is 7.71. From the data obtained F count < F table 5.501 < 7.71 then H0 is accepted and the decision taken is H0, which means there is no difference. From the results of the bending test, there is an effect of strength on ASTM A36 steel if it is seen that the average value of the bending test is significant. test Analysis of Variance. It is known that the calculated F is 21.711 and the F table is 7.71. From the data obtained, F count > F table, H0 is rejected and the decision taken is H1, which means that there is a difference in the average bending test using backing and without backing on ASTM A36 specimens.